A new species of Short Brown Unpatterned Moray Eel of the Genus Gymnothorax (Anguilliformes: Muraenidae) from the Bay of Bengal - Ray, Dipanjan; Mohapatra, Anil; Smith, David G. (Zootaxa, 2015)
A new species of short brown unpatterned moray eel of the genus Gymnothorax, Gymnothorax mishrai sp. nov. is described from a specimen of 324 mm total length, collected from the Bay of Bengal. The species is distinguished by having the dorsal-fin origin before gill opening, jaw pores with brown rim, two branchial pores, total vertebrae 134 (MVF: 9-59-134), three median intermaxillary teeth, uniserial maxillary and vomerine teeth. The new species is distinctly different from the other eight described species of this group. This species is also the first species of short brown unpatterned moray eel to be reported from India.